EVALUATION OF MASTICATORY FUNCTION IN PATIENTS WITH MAXILLARY DEFECTS AFTER RESECTION PERFORMED IN CONNECTION WITH THE CONSEQUENCES OF COVID-19 AFTER ORTHOPEDIC PROSTHETICS - Davron N. Xabilov (Central Asian Journal of Medicine, 2025)
The article deals with the problem of restoring masticatory function in patients with maxillary defects resulting from resection performed due to complications of COVID-19. The relevance of the study is determined by the need to develop effective approaches to rehabilitation of this category of patients suffering from a significant deterioration in the quality of life. Evaluation methods include clinical studies, instrumental tests, and subjective indicators that allow us to identify the dynamics of functional changes before and after prosthetics. The results of the study demonstrate an improvement in chewing efficiency, restoration of the symmetry of the chewing load and an increase in the level of comfort of patients. The data obtained emphasize the importance of orthopedic prosthetics in the comprehensive rehabilitation of patients with maxillary defects after resection associated with the consequences of COVID-19. The work is of practical value for specialists involved in restoring the functional and aesthetic characteristics of the oral cavity.